The impact of the PSPP on the European public debt markets : yields, spreads and liquidity - Jud, Dominic (2017)
This thesis analyzes the effects of the ECB’s Public Sector Purchase Programme (PSPP) on European public debt markets. Using a panel regression this study estimates the impact on yields, spreads and liquidity of European sovereign bonds. We find significant reductions in yields, a drop of 171 basis points on average across all countries, but spreads are not affected significantly. On liquidity, the evidence is mixed: we find that liquidity currently experiences higher volatility and more frequent disruptions, but it seems that ECB’s policy minimizes these issues. We conclude that the ECB was successful in decreasing funding costs for European countries and in stabilizing the debt markets. Furthermore, we do not see significant distortions of the market structure in terms of spreads. Lastly, we expect to see gradually increasing yields of the same magnitude and even higher volatility of liquidity after the policy is ended, whereas spreads will not change significantly, if the exit will be following the same timing and pace in all countries.